Value-based localization strategies of automobile subsidiaries in Thailand - Phallapa Petison (2010)
Purpose To analyze the scope of localization strategies and corresponding benefits of these strategies to subsidiaries of international companies in the automobile industry in Thailand. Design/methodology/approach The authors have adopted the case research method to investigate localization strategies of subsidiaries of seven companies (Toyota, Hino, Honda, Isuzu, DaimlerChrysler, BMW, and Auto Alliance) as well as 14 of their dealers and suppliers in Thailand. The information was gathered by conducting in-depth multiple interviews with 120 local and expatriate employees at various levels in the organizations; by referring to annual reports, policy documents and internal reports of these companies; and by observation during plant visits. Findings Contrary to the belief that international companies implement localization strategies to simply match the local market environment, it was found that these companies implement a wide range of localization strategies to achieve multiple benefits. The paper identifies nine areas of localization: localization of strategic decision making; building and exploiting the local knowledge pool; deployment of local human resources; localization of R&D; localization of products; use of local supplier networks; adaptations to manufacturing processes; local deployment of subsidiary profits; and localization of corporate image. These localization strategies are not just based on the principle of 3cost-based localization4 but are based on 3value-based localization.4 These strategies work in tandem and create value through a system of multiple benefits, such as managements' ability to comprehend and deal with uncertainty in the operating environment; make informed decisions to respond to challenges in developing efficient local assembly and marketing systems; cost reduction; higher degree of commitments by local employees; product customization and acceptance; and greater brand equity and image as a good corporate citizen. Practical implications Based on concrete illustrations of seven companies, this study identifies nine distinct areas for planning and implementing localization strategies and their corresponding benefits. The managers of subsidiaries can benefit by focusing their localization efforts in these areas to gain maximum advantage from host country context and then translate these advantages into a competitive international strategy. Originality/value CEOs of subsidiaries in emerging markets can learn how to build and harness local advantages for global competitiveness by implementing a wide range of localization strategies.